Reactions of BCl3 with Diiminopyridine Ligands. Issue 31 (6th August 2020) - Tidwell, John R.; Africa, Abigail K.; Dunnam, Thomas; Martin, Caleb D.
Abstract : The reactions of boron trichloride with diiminopyridine ligands featuring 2, 6‐diisopropylphenyl groups on the imine nitrogen atoms and varying groups on the α‐carbon atoms (H, CH3, and Ph) were investigated. N, N' ‐chelated cationic BCl2 complexes with BCl4 – counteranions were isolated with the hydrogen and phenyl‐substituted ligands while a mixture was obtained for the methyl variant. Abstract : The reactions of boron trichloride with diiminopyridine ligands featuring 2, 6‐diisopropylphenyl groups on the nitrogen atoms and varying groups on the α‐carbon (H, CH3, and Ph) were investigated. N, N' ‐chelated cationic BCl2 complexes with BCl4 – counteranions were isolated with the hydrogen and phenyl‐substituted ligands, while a mixture was obtained for the methyl variant.